VLSI for a new generation of microelectronic coordinate-sensitive etectors with an extended field of analysis for use in mass spectrometry - Sidorenko, V. P.; Radkevich, O. I.; Prokofiev, Yu. V.; Tayakin, Yu. V.; Virozub, T. M. (Technology and design in electronic equipment, 2018)
The authors have developed a custom VLSI chip for the new generation of MCSD devices - multichip detectors with an extended analysis field and higher technical characteristics, which can be used in elemental analysis devices to simultaneously determine the elements that make up the material with high sensitivity and accuracy in real time.VLSI chip contains 384 channels with a spatial resolution of 25 microns has been integrated onto a single chip, each channel has a metal anode to collect the electrons as they emerge from the microchannel plate electron multiplier (MCP); a charge sensitive amplifier to produce a digital signal in response to the electron pulse and a 16-bit counter associated with it to accumulate the counts as they arrive and circuitry to read out the data sequentially from all channels in the microcircuit. The VLSI chip is designed according to the design rules standard 1,0 μm CMOS process. The speed of the microcircuit in the counting mode is at least 15 MHz, in the mode of reading information from the counters - more than 10 MHz.The output from the 16-bit counters on the detectors is presented via an 8-bit port and is read into the control electronics sequentially from each counter in turn in low-byte, high-byte order.The circuit has been designed in such a way that an arbitrary number of detector chips may be abutted together on a substrate behind the MCP, allowing for long focal plane detectors to be built, limited only by the size of MCPs available.